Consistent abundance distributions of marine fishes in an old, climatically buffered, infertile seascape - Langlois, T.; Radford, B.; Van Niel, K.; Meeuwig, J.; Pearce, Alan; Rousseaux, C.; Kendrick, G.; Harvey, E. (Blackwell Science, 2012)
Aim: Macroecological theory predicts that along direct physiological gradients there will be unimodal abundance distributions of species and consistent rates of assemblage turnover. However, the majority of marine studies that have investigated the realized distribution of species along latitudinal or temperature gradients have generally found unimodal distributions to be rare. We assess fish distributions along a temperature gradient in a stable oligotrophic seascape and suggest that unimodal distributions will be more common. Location: Nearshore demersal fish habitat extending 1500 km along the coast of south-western Australia. Methods: The relative abundances of demersal fish species were sampled off the coast of south-western Australia along a temperature gradient. The confounding influence of other environmental variables was tested, and the assemblage was found to be highly correlated with temperature. For the 20 most abundant species, quantile regression spline models were used to construct a model within which 95% of their abundance was expected to fall. We compared the results from this study with the proportion of unimodal species abundance distributions observed in other studies.Results: Of the 20 most abundant species, 19 displayed patterns that indicated temperature was an important factor influencing their range and relative abundance; with 15 species exhibiting unimodal abundance distributions, four having ramped distribution to one end of the sampled range and one showing no consistent pattern. Main conclusions: The high diversity and percentage of endemic species in terrestrial and marine habitats of south-western Australia is likely to be due to the stable geological and oceanographic history of the region. In comparison, studies of abundance distribution in other marine systems have been conducted in relatively heterogeneous and productive environments. The old, climatically buffered, oligotrophic seascape of south-western Australia has provided a simple system in which the consistent influence of physiological gradients on the abundance distribution of fish species can be observed.